Qualitative assessment of knowledge and attitudes towards cervical cancer screening among male Latino immigrants in Houston, Texas - Susan H. Read; Ivan Valverde; Jane R. Montealegre; Thomas J. Rutherford; Matthew L. Anderson (BMC, 2020)
Abstract Background Male spouses and partners play an important role in determining a woman's willingness to participate in cervical cancer screening. However, the attitudes and behaviors by which they influence a woman's decision to undergo Pap testing remain poorly understood. Methods A series of semi-structured, qualitative interviews were conducted in Spanish with 19 recent Latino immigrants in Houston, Texas. The interview format was designed to establish each individual's pattern of engagement with the United States healthcare system, assess baseline knowledge of cervical cancer screening and evaluate attitudes and patterns of communication with their female partners regarding health care. Interview questions were constructed using principles of the Theory of Reasoned Action. All interviews were conducted in Spanish. After translation, responses were coded and scored with the goal of identifying themes and key observations. Results Most subjects reported few, if any, interactions with the healthcare system since their arrival in the United States. Although most participants reported being aware that women should be seen by their doctors regularly, fewer than half could clearly indicate the purpose of a Pap test or could state with certainty the last time their female partner had undergone screening. Multiple subjects expressed a general distrust of the health care system and concern for its costs. Approximately half of subjects reported that they accompanied their female partner to the health care provider's office and none of the participants reported that they were present in examination rooms at the time their partner underwent screening. Multiple participants endorsed that there may be some concerns within their community regarding women receiving frequent gynecologic care and distrust of the healthcare system. Almost all interviewed subjects stated that while they would allow their female partners to see male physicians, they also expressed the opinion that other men might be uncomfortable with this and that women would likely be more comfortable with female physicians. Conclusions Strategies to enhance knowledge of HPV and cancer screening and improve trust in the health care system among male spouses or partners should be explored with the goal of promoting cervical cancer screening among immigrant Latinx populations.